Pers dan Demokrasi Indonesia - Andi Alimuddin Unde (Magister Ilmu Politik Universitas Hasanuddin, 2016)
This paper describes the relationship between the press and the implementation of democracy in Indonesia. In this connection, newspaper as printed mass media have a responsibility to present information to the reader in tune with the cultural and social responsibility to the country and nation as a receiver of information. In the execution of the press has the potential to democratize the political life of the state or through the implementation of a number of functions. But, to build democracy, the execution of all functions of the press still encountered obstacles.In this study the authors conducted a study of literature through the study of literature well as direct observation related to democracy that occurred in Indonesia. Authors analyzed data obtained using the descriptive method with qualitative approach. The problems encountered in the implementation of all the functions of the press to build a democracy that is our nation's culture of communication that is still characterized by a closed mainly in the countryside is still dominant and the election officials who commit fraud are not necessarily sensitive to control and press criticism.In the presence of NGOs, the independent media, can more easily obtain accurate data on how the exercise of democracy.